Strategies in academic discourse - Tognini-Bonelli, Elena; Del Lungo Camiciotti, Gabriella (Studies in corpus linguistics, 2005)
This book focuses on theoretical and descriptive issues and techniques in the study of text and discourse. Drawing on a large number of corpora containing academic language, from spoken language to published research papers, the authors approach their subject from multiple angles: The academic language of biology, literature, philosophy, economics, agriculture, linguistics and applied linguistics. The analysis of intertextual features these papers show leads to penetrating results.